PENERAPAN ALGORITMA DEPTH-FIRST SEARCH DALAM SEBUAH WEBSITE BISNIS JARINGAN - , Kadek Indah Gunapriya Dharma Patmi, Ir. P. Insap Santosa, M.Sc., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
World wide web, internet, one of mainly need which commonly known in every individual or general purposes. Many things and value were ads on this virtual access, not only educated form however it becomes trade lines or purchase and sell access also. By purchase and sell web access, companies will get more chance to do many things and expand their networks trough new consumer within local scope, therefore many trades access and business needs commonly found in thus virtual access nowadays. One of their ways is networking business which commonly known as marketing network or multi level marketing. Companies which moves on trades by network access almost found complex problem, include when person come and would become a member of companies with lack information knowledge background. Just in case, one of member candidates only has sponsor ID. Many of company still hangs on manual system when faced up with this problem, call related company, find the position updates with manually up lines system and candidates will easily registered as a member. It would take and waste time, when its compared to the simply way pattern. Exclude percentage of calculation wages, transfer access and tree miss-plotting can be disoriented mind lines of company objectives. Related to this problem, a simply system would be built as a network business which involved certain method to get solution clear and out from the problem. On this thesis, researcher tried to engage simple finding methods with depth first search to help a trade wide site access get more effective profit, whereas this website system will apply multi information within by tree organizing although information gathering to produce system wedges calculation or any additional information use further. This way will give candidates and managers explore their process and interact in simple lines.